The Newfoundland and Labrador Health Accord - Stephen Bornstein (McMaster University Library Press, 2022)
In February 2022, a task force appointed by the Premier of Newfoundland and Labrador submitted a report that he had commissioned 14 months earlier. The task force's objective was to devise a 10-year strategy for modernizing and reforming the province's healthcare system and bringing health outcomes in the province up to Canada's high standards. The report will be followed this month (June 2022) by two more documents, an 'implementation blueprint' and an 'evidence report.' This commentary examines the report, summarizing both its devastating findings on the current health system and its comprehensive and ambitious proposals for reform.  En février la mi-novembre 2022, un groupe de travail nommé par le premier ministre de Terre-Neuve-et-Labrador a soumis un rapport commandé 14 mois plus tôt. L'objectif du groupe de travail était de concevoir une stratégie sur 10 ans pour moderniser et réformer le système de santé de la province et lui permettre de rattraper son retard sur les normes élevées du Canada pour ce qui est de la santé. Le rapport sera suivi, ce mois-ci (juin 2022), de deux autres documents, un « plan de mise en œuvre » et un «  rapport de preuves ». Ce commentaire examine le rapport, résumant à la fois son constat sévère sur le système de santé actuel et ses propositions de réforme ambitieuses dans tous les aspects du système.